Directions of Increasing the Effectiveness of Career Guidance System for Students in Russia - Vladimir AFANASIEV; Marina VRAZHNOVA; Mikhail NECHAEV; Svetlana FROLOVA; Liudmila SHYPOVSKAIA (Astra Salvensis, 2019)
The need to meet the world educational standards caused the actualization of the problem of improving the quality of vocational training in the higher education system. Studies have shown that the solution to this problem is closely related to the effectiveness of early career guidance work with students - future university students. In this regard, career guidance becomes one of the most important urgent tasks of the modern school. The purpose of the study is the theoretical and methodological substantiation of the system of psychological and pedagogical support of professional self-determination of students. Methods of the study: theoretical methods (study of theoretical sources and scientific publications, Internet resources, analysis, synthesis, generalization); diagnostic methods (questionnaire); statistical methods for processing experimental data. The result of the study was the substantiation of the need to develop a new career guidance system, a description of the history of the formation and development of career guidance in Russia, the definition of current trends in career guidance, a description of the existing career guidance model, identification of the main problems and the definition of methodological approaches to the development of the system of psychological and pedagogical support of professional self-determination of students.